Pergeseran Konflik Partai di Dapil I Kabupaten Tapanuli Utara pada Pemilu Legislatif 2014 - SITIO, RINALDI (Politeia: Jurnal Ilmu Politik, 2014)
Indonesia is a country that uses a democratic political system. Impact of that, this country organize general election periodically. General election held in Indonesia on April 2014. There are twelve parties and three Aceh Parties competing in this election. This study is about shift of party conflict in the Dapil I North Tapanuli in legislative elections 2014. Spesifically this study discussing about causes a shift of party conflict in the Dapil I North Tapanuli. This study is using political conclict as the approach and the data collection is using field research. The me-thod used is descriptive. Analysis is using qualitative technique. The finding of the study is there are three main causes of the conflict shifts. First, the impact of changes in the electoral system; secondly, ideological crisis of political parties; Third, the role of political parties and campaign process.Keywords: Conflict, Political Parties, Legislative Elections.